Metaphor Analysis in Political Discourse: A Comparative Study of the Chinese and Spanish Presidents - Xin, Dai (Sinología hispánica. China Studies Review, 2026)
Based on the conferences of the Chinese president Xi Jinping and the Spanish Pedro Sánchez during the period from 2018 to 2021, this work compares the metaphor in political discourse from the trinocular perspective. ‘From below’, the linguistic characteristic of metaphor is summarized, such as density, resonance and novelty in the Chinese and Spanish corpus; ‘from middle’, the systematic mapping is revealed to understand the cognitive thinking and psychological effect of the two leaders; and ‘from above’, the functions of metaphor are analyzed in reflecting the diplomatic relationship, the identity of the party, the interpersonal objective and the political panorama of the two countries. In this way, we are able to compare in depth the linguistic, cognitive and social aspects of the metaphors, as well as the political thoughts and governance concepts of China and Spain.